Fitness consequences of threshold trait expression subject to environmental cues - Michalczyk, Łukasz; Dudziak, Magdalena; Radwan, Jacek; Tomkins, Joseph L. (Proceedings of the Royal Society. B, Biological sciences, 2018)
Most cases of alternative reproductive tactics (ARTs) are thought to represent conditional strategies, whereby high-status males express highly competitive phenotypes, whereas males below a certain status threshold resort to sneaky tactics. The underlying evolutionarily stable strategy (ESS) model assumes that males of high competitive ability achieve higher fitness when expressing the territorial phenotype, whereas the less competitive males are more fit as sneakers, caused by fitness functions for the ARTs having different slopes and intersecting at a threshold value of competitive ability. The model, however, is notoriously difficult to test as it requires access to low-status territorials and high-status sneakers, that rarely occur in nature. Here, we test the conditional ESS in the androdimorphic acarid mite Sancassania berlesei , where large males tend to develop into an armoured, aggressive ‘fighter’ morph, while small males become unarmoured, non-aggressive ‘scramblers’. In addition to body size, male morph is affected by pheromones produced by big populations, with fighters being suppressed in dense colonies. By manipulating pheromone concentration, we obtained high-status scramblers and low-status fighters. We also estimated status- and size-dependent fitness functions for male morphs across a range of population sizes. Fighters had the highest fitness in small populations and their fitness declined with increasing density, whereas the reverse was true for scramblers, providing support for condition-dependent ESS with respect to demography. However, whereas male fitness increased with body size, the fitness functions did not differ significantly between morphs. Thus, although we found evidence for the intersection of morph fitness functions with respect to demography, we did not find such an intersection in relation to male body size. Our results highlight how demography can exert selection pressures shaping the evolution of the conditional strategy in species with ARTs.